Функціональне перетворення бітових потоків даних в апаратних online-обчислювачах математичних функцій - Ларченко, Б. Д. (ХНУРЕ, 2020)
This work offers and researches a reproduction approximation method of continuous ascending and descending functions of the determined class, optimal in accuracy and time of calculation. In specialized systems this method ensures a singular approach to function increment formation in pulse stream functional conversion. Function calculation error has been estimated.
Keywords: неперервні висхідні функції; оnline-обчислювачі відтворення